LoT-Based Integrated Environmental Monitoring System: Air Quality and Water Quality Control - Andrade Trujillo, Gilma Paola; Torres Silva, Pedro; Otavo Loaiza, Ronald Andrés (Ciencia y Reflexión, 2025)
The growth of urban and rural infrastructure has intensified problems with air and water quality, posing serious risks to public health and ecological systems. This paper describes the design, development and implementation of an environmental monitoring system aimed at real-time air and water quality analysis based on Internet of Things (IoT) technologies. The system includes two independent nodes that employ specialized sensors to capture critical variables such as PM2.5, CO2, pH, turbidity and dissolved oxygen, among others. The processed data is transmitted in real time using LoRa communication to a central ESP32-based gateway, which integrates the values into IoT platforms for analysis and visualization. The results obtained demonstrate the accuracy and effectiveness of the system, as well as its potential as a scalable tool for environmental management in urban and rural environments.